Sulfur heat transfer behavior for uniform and non-uniform thermal charging of horizontally-oriented isochoric thermal energy storage systems. (June 2020) - Barde, Amey; Nithyanandam, Karthik; Shinn, Mitchell; Wirz, Richard E.
Highlights: Sulfur is a low-cost storage medium for high-temperature TES. Experimental, analytical, computational methods reveal heat transfer behavior. Operating temperatures and mode of charging have strong impact on thermal charge rates. Superior performance for uniform thermal charging at high temperatures is achieved. Validated computational model is developed to design sulfur-based TES. Abstract: Elemental sulfur is a low-cost, chemically stable thermal storage medium suitable for many medium to high temperature applications. In this study, we investigate the heat transfer behavior of sulfur, isochorically stored in a horizontally-oriented thermal storage element (steel tube) using experimental, analytical, and computational methods. The sulfur container was uniformly and non-uniformly heated along its axis from 50 to 600 °C to simulate the potential operating conditions for the full-scale thermal energy storage systems. The results of the study reveal distinct sulfur heat transfer mechanisms based on the temperature range and mode of thermal charging. For temperatures from 50 to 200 °C, the sulfur heat transfer behavior is governed by two primary mechanisms; 1) solid–liquid phase change, and 2) sulfur viscosity that varies strongly with temperature. From 200 to 600 °C, the buoyancy-driven natural convection is the dominant heat transfer mechanism and facilitates significantly high thermal charge rates. For axially non-uniform thermal charging, the axial temperature gradient induces natural convection along the axis that rapidly redistributes the thermal energy within the sulfur mass. Such axial convection has a strong impact on the thermal characteristics, including thermal charge/discharge rate and exergetic efficiency of the thermal storage systems. These observations and the high-fidelity computational model used in this study provide important means to identify the design parameters and operating conditions for which sulfur-based thermal energy storage (SulfurTES) systems will provide desirable thermal performance at a low thermal storage cost.